DEVELOPMENT OF THE SERVICE SECTOR IN UZBEKISTAN: PRIORITY DIRECTIONS AND PROSPECTS - Khojalepesov Polat Zinatdinovich; Mambetsharipova Gulzada Polatbaevna; Mirzabaeva Ulzada Quwanishbaevna (Scholar Express Journals, 2025)
This article examines key aspects of the development of the service sector in Uzbekistan, its impact on the country’s economic growth, and the social wellbeing of citizens. Strategic initiatives aimed at modernizing the service sector are analyzed, including digitalization, the development of transport and tourism infrastructure, and the reform of financial and medical services. Special attention is given to the challenges faced by regions and government support measures aimed at increasing service volumes and attracting investments. Specific examples of successful projects are presented, along with recommendations for further improvement of the sector
Keywords: service sector; Uzbekistan’s economy; digitalization